Towards distinctive and developmental curricula at UoTs: The STEPS process at CUT - Mthembu, Thandwa (South African Journal of Higher Education, 2016)
In the first decade of this new century several policy changes have had a far-reaching impact on the South African higher education landscape (du Pré 2010). The former Technikons, themselves based on the previous colleges of the Advanced Technical Education, were empowered to award their own three and four year diplomas and became our current Universities of Technology (UoTs). Several of these were involved in mergers, with each other or traditional universities. Most recently the level and placement of these qualifications has been revisited in the Higher Education Qualifications Framework (2008), currently under review by the Council on Higher Education (CHE). These developments provide an opportunity for Universities of Technology (UoTs) to review who they admit and teach, what they teach, who teaches it, how they teach it, and what the overall outcomes should be. The prime purpose of UoTs such as CUT is to achieve a developmental impact through differentiated curricula (du Pré 2009): by admitting students with diploma- rather than degree-level university entry qualifications, and by equipping them with the qualification and graduate attributes that will, we would contend, actually secure them mid-level jobs and a viable career path. In this way, through its distinctive graduates, UoTs will make their primary contribution to the broader community. These tenets point to four important differences in the philosophical and practical approach at UoTs to curricula – by which are understood not only the subject matter and competences inculcated in a qualification, but the range of teaching and learning processes involved.